Turnover of professional nurses at Mokopane Hospital in the Limpopo Province, South Africa: Experiences of nursing unit managers - Mogale L. Mmamma; Tebogo M. Mothiba; Malema R. Nancy (AOSIS, 2015)
Background: Staff turnover of professional nurses remains a concern for public and private hospitals management because it has an impact on the morale of nurses and it may also lead to poor patient care. Objectives: The objectives of this study were to explore and describe the experiences of nursing unit managers with regard to the turnover of professional nurses who were under their supervision. Method: A qualitative, explorative, descriptive research design was used to determine the experiences of nursing unit managers related to the turnover of professional nurses. Data collection was done by using semi-structured one-to-one interviews with professional nurses .Two groups of participants were interviewed: Those working day duty (n = 9) and those working night duty (n = 3) who were at work on the anticipated days for data collection. Results: The findings revealed that every unit was experiencing a shortage of professional nurses, which caused other nurses to work overtime with an inevitable increase in workload. That led to tiredness, conflict amongst professional nurses, job dissatisfaction, and absenteeism which compromised nursing care. This resulted in patient dissatisfaction and sometimes led to deaths that could have been prevented. Conclusion: It is recommended that staff turnover should be addressed by the hospital top management implementing several strategies. For example, top management could ensure that staff members work in a healthy environment with resources that they need during the provision of care, address the effects of the staff turnover, support the staff members and refrain from putting pressure on nursing unit managers whilst they are attending to problems.